Design and Analysis of CO2 Refrigeration System for Indoor Ice Rink with Heat Recovery - Yao Yao; Li Minxia; Dang Chaobin; Dong Liwei; Ma Yitai; Tian Hua; Wang Pai (Zhileng xuebao)
The main energy requirements of indoor ice rinks are refrigeration and heat. If the refrigeration system can simultaneously meet the refrigeration and heating loads, the system efficiency can be significantly improved. In this study, the CO2 refrigeration system of an indoor ice rink with heat recovery is analyzed, considering an 1800 m2 ice hockey rink in Tianjin, China, as the research object. The actual comprehensive utilization coefficient (ACOPhc) is proposed. Four heat recovery systems that maximize the use of discharged heat were compared based on the actual heat consumption requirements of the system. The results demonstrate that the CO2 refrigeration system with heat recovery runs more smoothly. The two-stage compression refrigeration system of the ice rink that directly utilized the heat from the discharge gas leads to the highest annual operating efficiency of 6.77; in winter, this value can exceed 7.0.